John Searle’s Theory of Sign - Gvoždiak, Vít (Organon F, 2012)
The article attempts to link John Searle’s philosophy and the area that is traditionally called semiotics, to bridge these domains and to demonstrate that they do relate to a shared bunch of problems. A brief discussion about the basic semiotic terms suggests that Searle’s philosophy offers an explanatory framework to key semiotic questions, namely the differentiation of non-signs and signs, the place of intentionality in semiotic description, and the nature of sign correlations. As a consequence, Searle’s theory can be called communication-oriented semiotics, which in the light of classical concepts developed by Peirce and de Saussure can be seen as a non-trivial contribution to the semiotic research.
Keywords: arbitrariness; de Saussure Ferdinand; intentionality; Peirce Charles S.; representation; Searle John; semiotics; sign function